THE SURESH CASE AND UNIMPLEMENTED TREATY NORMS - Beaulac, Stéphane (Revue québécoise de droit international / Quebec Journal of International Law / Revista quebequense de derecho internacional, 2002)
This paper examines the role of unimplemented international treaty norms in the Canadian domestic legal system. The discussion focuses on the decision of the Supreme Court of Canada in Suresh, which is first investigated in some detail. In a unanimous judgement, it was held that the untransformed International Covenant on Civil and Political Rights and the Convention against Torture and other Cruel, Inhuman or Degrading Treatment or Punishment ought to inform the interpretation of the principles of fundamental justice in section 7 of the Charter and assist in deciding whether the exercise of power to deport under the Immigration Act was constitutional, given that the appellant could face torture if refoulé. The author refers to other recent decisions from the country’s highest court where unimplemented treaty obligations were used in the interpretation of Canada’s domestic law, namely, the Baker case in 1999 and the Hudson case in 2001. In conclusion, these developments are put in the broader contemporary strategy favouring contextual legislative interpretation, which includes resorting to international law, a trend that can be traced back to the adoption of the Charter in 1982.